Reconstruction of energy-dependent Sturm-Liouville equations from two spectra. II - Pronska, N.I. (Carpathian Mathematical Publications, 2013)
We study the problem of reconstruction of singular energy-dependent Sturm-Liouville equation from two spectra. We suggest a new method of solving this inverse problem by establishing its connection with the problem of reconstruction from one spectrum and the set of norming constants.